Transvenous lead extraction in children with bidirectional rotational dissection sheaths - Heck, Roland; Peters, Björn; Lanmüller, Pia; Photiadis, Joachim; Berger, Felix; Falk, Volkmar; Starck, Christoph; Kramer, Peter (Frontiers in Cardiovascular Medicine, 2023)
Objectives Due to the limited longevity of endovascular leads, children require thoughtful lifetime lead management strategies including conservation of access vessel patency. Consequently, there is an increasing interest in transvenous lead extraction (TLE) in children, however, data on TLE and the use of powered mechanical dissection sheaths is limited. Methods We performed a retrospective cohort study analyzing all children <18 years that underwent TLE in our institution from 2015 to 2022. Procedural complexity, results and complications were defined as recommended by recent consensus statements. Results Twenty-eight children [median age 12.8 (interquartile range 11.3–14.6) years] were included. Forty-one leads were extracted [median dwell time 85 (interquartile range 52–102) months]. Extractions of 31 leads (76%) in 22 patients (79%) were complex, requiring advanced extraction tools including powered bidirectional rotational dissection sheaths in 14 children. There were no major complications. Complete procedural success was achieved in 18 (64%) and clinical success in 27 patients (96%), respectively. Procedural success and complexity varied between lead types. The Medtronic SelectSecure™ lead was associated with increased odds of extraction by simple traction (p = 0.006) and complete procedural success (p < 0.001) while the Boston Scientific Fineline™ II lead family had increased odds of partial procedural failure (p = 0.017). Conclusions TLE with the use of mechanical powered rotational dissection sheaths is feasible and safe in pediatric patients. In light of rare complications and excellent overall clinical success, TLE should be considered an important cornerstone in lifetime lead management in children. Particular lead types might be more challenging and less successful to extract.